Diagnosis of systemic candidiasis by an enzyme-linked dot immunobinding assay for a circulating immunodominant 47-kilodalton antigen. - Matthews, R (1988)
A dot immunobinding assay based on the detection of the immunodominant 47-kilodalton (kDa) antigen of Candida albicans is described for the serological diagnosis of systemic candidiasis. It was compared with a reverse passive latex agglutination test and a dot immunobinding assay with total unfractionated hyperimmune serum to C. albicans. Use of the 47-kDa antigen-specific probe increased both the sensitivity and specificity of the assay system. Patients with systemic candidiasis were detected earlier in the course of the infection. The rate of detection of systemic C. albicans infections in neutropenic patients was 77% compared with 55% with total antibody in the dot immunobinding assay and 29% with the latex test. All three assay systems were positive in over 73% of infected patients who were not neutropenic. The 47-kDa antigen-specific probe was relatively specific to C. albicans. Antibody probes to the immunodominant antigens of other yeasts might be incorporated in the same dot immunobinding assay to detect systemic candidiasis caused by other species of yeasts.